ISOTOPIC COMPOSITION OF GYPSUM SAMPLES OF PERMIAN AND TRIASSIC AGE FROM THE NORTH-EASTERN ITALIAN ALPS: PALAEOENVIRONMENTAL IMPLICATIONS - Longinelli A.; Flora O. (My University, 2007)
Over the last fifty years, only relatively few measurements have been carried out on the oxygen isotopic composition of evaporite sediments, probably because of the technical problems related to these measurements, among other reasons. To make a further contribution to our knowledge of δ18O values of seawater sulphate through time, we report here the results obtained from forty gypsum samples of Permian and Triassic age coming from the north-eastern section of Italian Alps. The δ18O values of the samples of Permian age range from 15.4 to 17.9‰ (VSMOW) with a mean value of 16.7‰, while the samples of Triassic age range from 11.7 to 16.3 with a mean value of 14.7‰. The δ34S values measured on four samples for each group to provide indirect confirmation of the age of the samples yield homogeneous results, with mean values of 11.8‰ vs. VCDT (Permian) and 15.0‰ (Triassic). Both these values agree with the sulphur isotope age curve. The isotopic signatures of our samples seem to be well preserved and the reported values are in reasonable agreement with previous results. The interpretation of our data fits well in the framework of the global sulphur cycle and the reported values can be reasonably considered to represent the isotopic composition of oceanic sulphate during the related geologic periods. © 2007 Elsevier B.V. All rights reserved.
Keywords: NORTH-EASTERN ITALIAN ALPS; OXYGEN ISOTOPES; PERMIAN GYPSUM; SULPHUR ISOTOPES; TRIASSIC GYPSUM; Triassic; Permian; Mesozoic::Triassic; Мезозой::Триасовая; Paleozoic::Permian; Палеозой::Пермская